2019
DOI: 10.3390/nu11081729
|View full text |Cite
|
Sign up to set email alerts
|

Cereal B-Glucans: The Impact of Processing and How It Affects Physiological Responses

Abstract: Cereal β-glucans are dietary fibres primarily found in oats and barley, and have several positive effects on health, including lowering the postprandial glucose response and the improvement of blood cholesterol levels. Cereal β-glucans have a specific combination of β-(1→4) and β-(1→3) linkages into linear long-chain polysaccharides of high molecular weight. Due to their particular structure, cereal β-glucans generate viscosity within the intestinal tract, which is thought to be the main mechanism of action re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 76 publications
(113 reference statements)
0
84
0
1
Order By: Relevance
“…The higher viscosity also slows the gastric emptying process down and reduces the rate of starch digestion (and associated mono- and disaccharide production) and, hence, causes a delay in glucose absorption [ 114 ]. The slower digestion rate can also be the result of the formation of a ‘thick layer’ around the food bolus, that reduces the access digestive enzymes have to the inner part of the food bolus and hinders contact with absorbing surfaces in the gastrointestinal tract [ 115 , 116 ]. Even though SDF are considered to display anti-diabetic effects, it has been found that IDF are more potent in reducing the risk of type 2 diabetes [ 117 , 118 ].…”
Section: Dietary Fibre From Whole Grains and Health Implicationsmentioning
confidence: 99%
“…The higher viscosity also slows the gastric emptying process down and reduces the rate of starch digestion (and associated mono- and disaccharide production) and, hence, causes a delay in glucose absorption [ 114 ]. The slower digestion rate can also be the result of the formation of a ‘thick layer’ around the food bolus, that reduces the access digestive enzymes have to the inner part of the food bolus and hinders contact with absorbing surfaces in the gastrointestinal tract [ 115 , 116 ]. Even though SDF are considered to display anti-diabetic effects, it has been found that IDF are more potent in reducing the risk of type 2 diabetes [ 117 , 118 ].…”
Section: Dietary Fibre From Whole Grains and Health Implicationsmentioning
confidence: 99%
“…But, there is no sufficient information available on how processing, such as flaking, affects the chemopreventive effects of oat and barley products. The effects of processing on physicochemical properties such as viscosity and the resulting impact on physiological effects such as cholesterol and glycaemic response-lowering capacity have been extensively studied for different types of oat and barley products and in different types of studies [14][15][16][17][18][19][20]. For example, flaking involves heat-moisture treatments, which modify the physicochemical characteristics of β-glucan such as molecular weight and viscosity [21].…”
Section: Introductionmentioning
confidence: 99%
“…Barley and oats are rich in β-glucan, which has several positive effects on inhibiting a postprandial glucose rise [ 1 , 2 , 3 ] and improvement in serum cholesterol concentrations [ 4 , 5 , 6 , 7 , 8 ]. Barley and oat β-glucans have β-1,3 and β-1,4 glycosidic polysaccharides with high molecular weight [ 9 , 10 ]. It is generally recognized that β-glucans in barley and oats with higher molecular weights are essential for a reduction in postprandial blood glucose rise and incremental area under the blood concentration curve (IAUC) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%